Benchmark experiments for higher-order and full Stokes ice sheet models (ISMIP-HOM) - Pattyn, F.; Perichon, L.; Aschwanden, A.; Breuer, B.; de Smedt, B.; Gagliardini, O.; Gudmundsson, G. H.; Hindmarsh, R.; Hubbard, A.; Johnson, J. V.; Kleiner, T.; Konovalov, Y.; et al. (HAL CCSD, 2008)
International audience We present the results of the first ice sheet model intercomparison project for higher-order and full Stokes ice sheet models. These models are validated in a series of six benchmark experiments of which one has an analytical solution under simplifying assumptions. Five of the tests are diagnostic and one experiment is prognostic or time dependent, for both 2-D and 3-D geometries. The results show a good convergence of the different models even for high aspect ratios. A clear distinction can be made between higher-order models and those that solve the full system of equations. The latter show a significantly better agreement with each other as well as with analytical solutions, which demonstrates that they are hardly influenced by the used numerics.